Risk factors of treatment-limiting anemia after substitution of zidovudine for stavudine in HIV-infected adult patients on antiretroviral treatment. - Thong Phe (Public Library of Science (PLoS), 2013)
Background Anemia is the main concern among patients using a zidovudine (AZT)-based antiretroviral treatment (ART). Some studies suggested weight-adjusted AZT dosing as a way to reduce toxicity. We analyzed the risk factors associated with AZT-induced anemia in a cohort using AZT as substitution for stavudine (D4T). Methods We retrospectively studied HIV-infected patients in a referral hospital in Phnom Penh, Cambodia between 2003 and 2011. Factors associated with AZT-related anemia requiring AZT-discontinuation within the first year after AZT initiation were analyzed using Cox regression. Results Overall, 1180 patients, 60.5% female, were included. At AZT initiation, the median hemoglobin was 12.7 g/dL (IQR 11.7-13.9), the median weight: 51 kg (IQR 45-58) and the median time on ART prior to AZT substitution: 1.4 years (IQR 1.0-2.0). Within one year follow-up, 139 patients (11.8%) developed anemia requiring AZT discontinuation. Overall, there was no independent association of body weight with AZT discontinuation. AZT discontinuation was associated with lower hemoglobin level when starting AZT; older age and taking D4T-based ART less than one year prior to AZT. In exploratory analysis, a linear increase in risk of grade 2-4 anemia with lower body weight was seen if starting AZT substitution within less than one year of D4T-based ART. Conclusion Our findings argue against the need of weight-based dosing of AZT to reduce anemia among patients using AZT as substitution for D4T. Whether this also applies to ART-naïve individuals remains to be assessed. Future studies with AZT dose reduction should assess efficacy and overall tolerance of AZT.